2003
DOI: 10.1038/sj.onc.1206263
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2-dependent and independent formation of RAD51 nuclear foci

Abstract: The formation of RAD51 foci in response to ionizing radiation (IR) represents an important step in the repair of DNA double-strand breaks. RAD51 foci also appear during S phase and are thought to be required for the restart of stalled or broken replication forks. The RAD51 recombinase interacts directly with the breast cancerassociated tumour suppressor BRCA2, an interaction that is required for normal recombination proficiency, radiation resistance and genome stability. In CAPAN-1 cells, which express a trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(154 citation statements)
references
References 41 publications
11
142
0
1
Order By: Relevance
“…Thus, it is of interest to study whether c-ABL has any effects on in vivo behaviors of self-association-defective RAD51 mutants. Since RAD51filament formation in vivo is a complex cellular process, especially in higher vertebrate cells, requiring transport to and assembly in chromatin, before RAD51 nucleoprotein filament formation on damaged DNA [14,20], we examined effects of c-ABL on nuclear transport or chromatin association of RAD51. HA-tagged RAD51-WT or RAD51-R167G was transiently co-expressed with Flag-tagged active (wt) or kinase-dead (kd) c-ABL in 293T cells, and cells were fractionated into cytoplasmic, nuclear and chromatin-associated fractions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is of interest to study whether c-ABL has any effects on in vivo behaviors of self-association-defective RAD51 mutants. Since RAD51filament formation in vivo is a complex cellular process, especially in higher vertebrate cells, requiring transport to and assembly in chromatin, before RAD51 nucleoprotein filament formation on damaged DNA [14,20], we examined effects of c-ABL on nuclear transport or chromatin association of RAD51. HA-tagged RAD51-WT or RAD51-R167G was transiently co-expressed with Flag-tagged active (wt) or kinase-dead (kd) c-ABL in 293T cells, and cells were fractionated into cytoplasmic, nuclear and chromatin-associated fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Transient transfection were performed by using FuGENE 6 Transfection Reagent (Roche). Subcellular fractionation was carried out essentially as described [14].…”
Section: Methodsmentioning
confidence: 99%
“…It also directly interacts with the recombinase and could participate in its nuclear localization (Davies et al, 2001;Pellegrini et al, 2004). However, nuclear foci of Rad51 are also observed during S phase independently of the presence of Brca2, suggesting that distinct pathways, requiring different proteins, could contribute to Rad51 foci formation in S phase or following DNA-damaging treatments (Tarsounas et al, 2003). Brca1 colocalizes with Rad51 in S phase and following DNA-damaging treatments (Scully et al, 1997), but this interaction is thought to be indirect and mediated by Brca2 (Venkitaraman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They are also in agreement with the results of Tutt et al (2001) who found that gene conversion was significantly reduced in BRCA2-deficient cells, while levels of SCE were only slightly reduced. Previously, it has been reported that RAD51 foci are formed in BRCA2-deficient cells in the S phase of the cell cycle (Tarsounas et al, 2003), suggesting that these cells may still repair DSBs at replication forks. It has also been shown that DSBs induced at replication forks preferentially trigger SCE rather than gene conversion (Arnaudeau et al, 2001;Saleh-Gohari and Helleday, unpublished).…”
Section: Suppressed Short Tract Gene Conversion (Stgc) But Not Sce Imentioning
confidence: 99%
“…Furthermore, translocation of the RAD51 protein to the nucleus is dependent on BRCA2 (Davies et al, 2001), and RAD51 foci fail to form in response to DNA damage in BRCA2-defective cells (Kraakman-van der Zwet et al, 2002). However, it has been shown that some RAD51 foci form independent of a functional BRCA2 protein during the S phase of the cell cycle, although damage-induced RAD51 foci fail to form in the same BRCA2-deficient cells (Tarsounas et al, 2003). From these data it has been suggested that there may be two ways to form RAD51 foci, dependent or independent of a functional BRCA2 protein.…”
mentioning
confidence: 99%